Developing a Digital Story for Engaged Student Learning - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2012)
Once upon a time, a long long time ago, in a classroom far far away, teachers don’t have fancy animated slides, textbooks, projectors or even whiteboards… they simply share their knowledge by telling stories. Now, with all the technologies at our disposal, we can tell more engaging stories and engage our students in the digital realm. This presentation is about a 12-episode (spanning a storyline of 2-3 years) digital story that helps students understand how accounting can make the difference in running a successful business venture. We hope to rekindle your interest in telling stories! The first four episodes of our MD2D story can be viewed at www.research.smu.edu.sg/faculty/MD2D/.